Greedy Algorithm - Jain, Abhishek; Saini, Manjeet; Kumar, Manohar (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2015)
This paper describes the basic technological aspects of algorithm, algorithmic efficiency and Greedy algorithm. Algorithmic efficiency is the property of an algorithm which relate to the amount of resources use by the algorithm in computer sciences. An algorithm is considered efficient if its resource consumption (or computational cost) is at or below some acceptable level.